Noa : sistema interactivo para la preparación y acompañamiento en procesos de vacunación infantil (2019)
Purpose - ​This design project, and the study that resulted of it, seeks to explore how previous preparation strategies, such as: facilitating access to vaccination information, increasing familiarization with the vaccination tools and procedure, and undergoing drill vaccination experiences; can serve as a means to help children around the age of five, and their parents, to be better cognitively and emotionally equipped to undergo the children’s future vaccination procedures. The main objective is to reduce the feelings of fear and anxiety experienced during children's vaccination and by doing so reducing the chances of developing current or future complications such as: bad vaccination procedures, needle phobia, aversion feelings to needle-based procedures, and the reduction of properly immunized population. Design/methodology/approach - ​This project is of a qualitative, descriptive and interpretive nature. The data collected and the conclusions reached through the various method tools used, are both descriptive, and they seek to provide an in depth understanding of the subjective variables present around the experiences of children's vaccination. The applied methodology for the development of this project was based on the Double Diamond design process proposed by the Design Council. In which the design process is broken into fours pages: Discover, Define, Develop and Deliver. Translated in this study to: Research, Analysis, Ideation and Prototyping.